An adolescent with an asymptomatic adnexal cyst: To worry or not to worry? Medical versus surgical management options - De Sanctis, Vincenzo; Soliman, Ashraf T; Elsedfy, Heba; Soliman, Nada A; Elalaily, Rania; Di Maio, Salvatore; Ahmed, Alaa Y; Millimaggi, Giuseppe (Acta Biomedica Atenei Parmensis, 2017)
Paraovarian cysts or paratubal cysts (PTCs) arise from either the mesothelium or from paramesonephric remnants. These present as either adnexal mass or as an incidental finding. Diagnosis is usually established on ultrasound and it is important to differentiate these from ovarian cysts. Typically PCTs appear as simple cysts by ultrasound and are indistinguishable from ovarian cysts if one does not recognize the extraovarian location. Occasionally, PTCs have internal echoes due to hemorrhage. PTCs are usually asymptomatic and benign. The differential diagnosis includes a simple ovarian cyst, peritoneal inclusion cyst and hydrosalpinx. Malignant changes have been reported in about 2% to 3%, and it should be suspected if papillary projections are present. PTCs management depend upon the presence and severity of the symptoms, the cyst size and US characteristics, CA 125 results, age of the patient and the risk of malignancy. Simple PTCs can be expected to regress and may be managed expectantly. When surgery is indicated, a joint multidisciplinary management by the paediatric surgeons and trained paediatric gynaecologists should be the gold standard.